Relative Abundance of Carsonella ruddii (Gamma Proteobacterium) in Females and Males of Cacopsylla pyricola (Hemiptera: Psyllidae) and Bactericera cockerelli (Hemiptera: Triozidae). Issue 1 (6th June 2015) - Cooper, W. Rodney; Garczynski, Stephen F.; Horton, David R.
Abstract : Carsonella ruddii (Gamma Proteobacterium) is an obligate bacterial endosymbiont of psyllids that produces essential amino acids that are lacking in the insect's diet. Accurate estimations of Carsonella populations are important to studies of Carsonella -psyllid interactions and to developing ways to target Carsonella for control of psyllid pests including pear psylla, Cacopsylla pyricola (Förster) (Hemiptera: Psyllidae) and potato psyllid, Bactericera cockerelli (Šulc) (Hemiptera: Triozidae). We used two methods, namely fluorescence in situ hybridization and quantitative polymerase chain reaction (qPCR), to estimate relative abundance of Carsonella in bacteriocytes and whole bodies of psyllids, respectively. Using these two methods, we compared Carsonella populations between female and male insects. Estimations using fluorescence in situ hybridization indicated that Carsonella was more abundant in bacteriocytes of female C. pyricola than in those of males, but Carsonella abundance in bacteriocytes did not differ between sexes of B. cockerelli . Analyses by qPCR using whole-body specimens indicated Carsonella was more abundant in females than in males of both psyllids. Neither fluorescence in situ hybridization nor qPCR indicated that Carsonella populations differed in abundance among adults of different ages (0–3 wk after adult eclosion). Using fluorescence in situ hybridization, Carsonella was observed in ovarioles of newly emerged females and formed an aggregation in the posterior end of mature oocytes. Results of our study indicate that female psyllids harbor greater populations of Carsonella than do males and that sex should be controlled for in studies which require estimations of Carsonella populations.